Canadian Immigration Experience: Any Lessons for Europe? - Don J. DeVoretz; Samuel A. Laryea (Institute for the Study of Labor (IZA), 1999)
This paper reviews and analyzes the effects of Canada?s post World War II immigration policies with the perspective of what European policy makers can learn from this experience. Impact of Immigration on natives? employment and earnings, as well as, immigrants? labor market experiences are discussed. The advantages of Canada?s equal share rule of the allocation of immigrant visas are argued. The importance of language skills for economic integration and success is also stressed. The importance of the right human capital mix and experience are found to be needed to guarantee positive labor market outcomes in the host country.
Keywords: J68; J61; J15; 330; Immigration policy; labor outcomes; assimilation; Migrationspolitik; Internationale Arbeitsmobilität; Arbeitsmarkt; Arbeitslosigkeit; Lohn; Soziale Integration; Schätzung; Kanada